Economia como fio condutor: dos estudos arqueológicos à governamentalidade liberal em Michel Foucault - Arantes de Souza, Lívia Francisco (Universidade Federal de São Carlos, 2026)
This work investigates Michel Foucault's thought, taking as its guiding thread his approach to economic discourses and practices from the archaeological studies of the 1960s to the courses on governmentality of the late 1970s. It addresses (i) the importance of the economic and social conjuncture for what made possible the fall of the human into objectivity (History of Madness); the relationship of economics with (ii) the epistemological imprisonment of the human within its finitude, and the aspects that mark the discontinuity between the analysis of wealth and political economy (The Order of Things); (iii) economic aspects of the relationship between disciplinary mechanics and the emergence of the human sciences (lectures from the first half of the 1970s); (iv) the importance of the economic grasp of the population for the biopolitical consideration of mass human phenomena, and as an organizing axis in terms of the shift away from what serves as the epistemological foundation for the human sciences (lectures from the late 1970s). In light of these aspects, it is argued that relating Foucault's gesture, in the late 1970s, of granting considerable importance to economic liberalism for his diagnosis of the present with his earlier efforts is a way of making explicit the consistency of his work and of avoiding the pitfalls of commentaries that glimpse in his reading of economic liberalism a sign of admiration and political adherence.
Economy as a guiding thread: from archaeological studies to liberal governmentality in Michel Foucault
Keywords: Antropologia; Humanismo; Economia política; Liberalismo Econômico; CIENCIAS HUMANAS::FILOSOFIA; 4. Educação de Qualidade